From implementation to discontinuation: multi-year experience with the multiple sclerosis performance test as a digital monitoring tool - Schriefer, Dirk; Dillenseger, Anja; Atta, Yassin; Inojosa, Hernan; Ziemssen, Tjalf (Frontiers in Digital Health, 2025)
IntroductionDigital tools such as the self-administered Multiple Sclerosis Performance Test (MSPT) support structured monitoring of multiple sclerosis (MS) through standardized assessments of motor, visual, and cognitive functions. Despite clinical validity and adoption, real-world data on long-term user experiences and the consequences of discontinuing MSPT-based monitoring in routine care are lacking.ObjectiveThis study aimed to assess multi-year user experiences with the MSPT among patients and neurologists, investigate patient perceptions following its discontinuation from clinical care, and evaluate preferences for future MSPT-like digital tools.MethodsThis observational, repeated cross-sectional study involved three questionnaire-based surveys. In 2020, separate surveys of patients and neurologists (combined n = 210) evaluated sustained MSPT use in routine care. Following the cessation of funding and subsequent discontinuation of MSPT from clinical workflows in 2023, a patient survey was conducted in 2024 (n = 144) to evaluate the impact of this withdrawal and preferences for future digital monitoring tools. Quantitative analyses included frequency distributions, Net Promoter Score (NPS) categorization, correlational analyses, and descriptive data visualization.ResultsPatients reported high satisfaction with MSPT usability, utility for disease monitoring, administration frequency, time efficiency, physical and cognitive demands, and suitability for unsupervised tablet-based use. Most viewed discontinuation from their clinical care negatively and favored reintroducing similar tools, either in clinic (85.5%) or at home (78.6%). Those who dissented cited time savings and sufficient physician feedback.DiscussionProlonged MSPT use is associated with strong patient and clinician acceptance. Findings support the continued integration of digital monitoring tools into MS care and emphasize the importance of patient perspectives in their design.